Developing Biak-Numfor as a National Tourism Magnet: Strategies for Tourism Destination - Arnie Arief; Muchammad Makkah Arief; Ali Muhtasom; Masri Ridwan (PINISI Discretion Review, 2023)
Tourism has emerged as a significant economic sector worldwide, contributing to job creation, foreign exchange earnings, and overall development. In Indonesia, the government recognizes the potential of tourism and aims to develop various destinations to attract both domestic and international travelers. This research focuses on the development of Biak-Numfor as a national tourism magnet, analyzing strategies to enhance its tourism potential. The study employs a qualitative research methods. Data collection involves surveys, interviews, and analysis of secondary data from tourism-related sources. The research identifies the key strengths, weaknesses, opportunities, and threats (SWOT) of Biak-Numfor as a tourism destination, considering factors such as natural resources, cultural heritage, infrastructure, accessibility, and competitive advantage. Based on the SWOT analysis, strategic recommendations are proposed to leverage the tourism potential of Biak-Numfor. These recommendations encompass four key areas: infrastructure development, cultural preservation and promotion, marketing and branding, and community involvement. The research emphasizes the importance of sustainable tourism practices, community engagement, and collaboration between stakeholders to ensure the long-term success of the destination. Furthermore, the study examines successful case studies from other similar destinations and explores their strategies for tourism development. Lessons learned from these cases serve as valuable insights for Biak-Numfor's tourism planning and implementation. The findings of this research contribute to the existing body of knowledge on tourism destination development and provide practical recommendations for policymakers, tourism industry stakeholders, and local communities in Biak-Numfor. By implementing the proposed strategies, Biak-Numfor has the potential to become a prominent national tourism magnet, attracting both domestic and international tourists, stimulating economic growth, and preserving its unique natural and cultural heritage.